Reasons for admission to a general medical hospital for patients taking clozapine - Siobhan Gee; Vasco Almeida; Adam Hughes; Isabel McMullen; David Taylor (SAGE Publishing, 2022)
Background: Clozapine is associated with a diverse range of side effects. In addition, patients prescribed clozapine commonly suffer with medical comorbidities. Objectives: This study aimed to characterise patients prescribed clozapine who required medical admission, understand reasons for admission, identify areas for interventions to prevent future admission and describe clozapine management during the inpatient stay. Design: We conducted a retrospective analysis of patients prescribed clozapine who were admitted to a general medical hospital in a 12-month period. Method: Data were collected using electronic drug charts and notes. Results: In total, 114 clozapine patients were hospitalised. Twenty-eight patients (25%) were admitted because of infection, 12 (11%) were elective admissions and 12 (11%) had gastrointestinal problems. Most patients admitted were Black (54%) and half were female. Few changes were made to clozapine dosing on admission or during the inpatient stay. Most patients had been taking clozapine for many years at the point of admission, the majority were able to continue taking it for the duration of their medical treatment and were discharged on the same dose they were taking prior to admission. Clozapine plasma concentrations were not consistently measured with only 18 (16%) patients having one or more plasma concentrations determined during their admission. The median clozapine plasma concentration on admission was 0.48 mg/L (nor-clozapine 0.21 mg/L), with a range of 0.09 to 3.9 mg/L. Three patients were admitted to the intensive care unit during their admission; all were discharged on clozapine. Four patients died; one from lung adenocarcinoma, one bowel obstruction, one cardiac arrest and one chest sepsis. In total, 27 patients (23%) had their clozapine stopped on admission, 6 (22% of this group) unintentionally. Conclusions: Our study found that the most common reason for admission for patients taking clozapine was infection. Plasma concentrations were not measured routinely despite clozapine having a narrow therapeutic index and enhanced potential for toxicity in the medically unwell patient.